KONSELING PANCAWASKITA: MASIDU UNTUK MENANGANI MOTIVASI BELAJAR RENDAH SISWA MTS SABILUL HUDA CANGKRING KARANGANYAR KABUPATEN DEMAK TAHUN AJARAN 2016/2017 - Anas Rohman (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2017)
In the learning activities in school is not uncommon found that students whoselearning achievement is low, not really in learning and do not have the spirit of learning. It issaid to be students who have low learning motivation, so guidance and counseling servicesare needed. One of them with Counseling pancawaskita: Masidu. Counseling pancawaskita:Masidu, is an eclectic counseling can help counselees personally to get out of the problemsfaced. In essence counseling pancawaskita: masidu, is a counseling that changed the oldgatra konseli into a new positive gatra so that the counselee can independently understandthe meaning of in himself and the meaning of a positive outside with a professional counselorwho clairvoyant. Research problem: How to Counseling Pancawaskita: Masidu to handle lowlearning motivation, students of class VIII MTs Sabilul Huda Cangkring KaranganyarDistrict Demak Lesson 2016/2017. Qualitative research method using documentation,interview and observation method. The result of research 1. Conseli I (AM) experiencing lowlearning motivation influenced by internal factor (Masidu) that is in him there is no spirit oflearning and does not attach importance to study. Spending more time with friends until lateat night and no time to study, often sleepy during the learning process. 2. Conseli II (USA)experiencing low learning motivation is influenced by internal factors (Masidu) is not like theEnglish lesson so that in him there is no spirit to learn English. Do not have the spirit oflearning and the responsibility to study seriously (the spirit of learning that withered). 3.Conseli III (MD) experiencing low learning motivation influenced by internal factor (Masidu)that is experiencing the spirit of learning that wilted in him there is no spirit to learnearnestly. Can not forget her boyfriend even though MD is betrayed and abandoned so thatMD does not have the spirit of learning and responsibility to study seriously .. Efforts to helpcounselees who have low learning motivation of providing individual counseling services byusing counseling pancawaskita and the results of the counselee independently understandhimself and can come out Of the problem.Key Words : Pancawaskita Counseling, Low learning motivation